Blood Management in Total Knee Arthroplasty: A Nationwide Analysis from 2011 to 2018 - Warren, Jared A.; McLaughlin, John P.; Molloy, Robert M.; Higuera, Carlos A.; Schaffer, Jonathan L.; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2020)
Both advances in perioperative blood management, anesthesia, and surgical technique have improved transfusion rates following primary total knee arthroplasty (TKA), and have driven substantial change in preoperative blood ordering protocols. Therefore, blood management in TKA has seen substantial changes with the implementation of preoperative screening, patient optimization, and intra- and postoperative advances. Thus, the purpose of this study was to examine changes in blood management in primary TKA, a nationwide sample, to assess gaps and opportunities. The American College of Surgeons National Surgical Quality Improvement Program database was used to identify TKA (n = 337,160) cases from 2011 to 2018. The following variables examined, such as preoperative hematocrit (HCT), anemia (HCT <35.5% for females and <38.5% for males), platelet count, thrombocytopenia (platelet count < 150,000/µL), international normalized ration (INR), INR > 2.0, bleeding disorders, preoperative, and postoperative transfusions. Analysis of variances were used to examine changes in continuous variables, and Chi-squared tests were used for categorical variables. There was a substantial decrease in postoperative transfusions from high of 18.3% in 2011 to a low of 1.0% in 2018, (p < 0.001), as well as in preoperative anemia from a high of 13.3% in 2011 to a low of 9.5% in 2016 to 2017 (p < 0.001). There were statistically significant, but clinically irrelevant changes in the other variables examined. There was a HCT high of 41.2 in 2016 and a low of 40.4 in 2011 to 2012 (p < 0.001). There was platelet count high of 247,400 in 2018 and a low of 242,700 in 201 (p < 0.001). There was a high incidence of thrombocytopenia of 5.2% in 2017 and a low of low of 4.4% in 2018 (p < 0.001). There was a high INR of 1.037 in 2011 and a low of 1.021 in 2013 (p < 0.001). There was a high incidence of INR >2.0 of 1.0% in 2012 to 2015 and a low of 0.8% in 2016 to 2018 (p = 0.027). There was a high incidence of bleeding disorders of 2.9% in 2013 and a low of 1.8% in 2017 to 2018 (p < 0.001). There was a high incidence of preoperative transfusions of 0.1% in 2011 to 2014 and a low of <0.1% in 2015 to 2018 (p = 0.021). From 2011 to 2018, there has been substantial decreases in patients receiving postoperative transfusions after primary TKA. Similarly, although a decrease in patients with anemia was seen, there remains 1 out 10 patients with preoperative anemia, highlighting the opportunity to further improve and address this potentially modifiable risk factor before surgery. These findings may reflect changes during TKA patient selection, optimization, or management, and emphasizes the need to further advance multimodal approaches for perioperative blood management of TKA patients. This is a Level III study.
Keywords: Blood Management; transfusion; anemia; knee; total knee arthroplasty